2016
DOI: 10.5688/ajpe80350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Tabletop Emergency Preparedness Exercise for Pharmacy Students

Abstract: Objective. To describe the implementation and effect of an emergency preparedness laboratory activity on student knowledge, willingness to participate in emergency preparedness training, current level of preparedness, and the importance of a pharmacist's role in disaster response. Design. Second-year pharmacy students in the infectious disease module participated in a laboratory activity based on a basic disaster response tabletop exercise format. Three case-based scenarios involving infectious diseases were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
0
22
0
3
Order By: Relevance
“…DeGuire et al 40 Despite the fluctuations in emphasis on public health and EP&R training in the CAPE Outcomes and ACPE Standards, pharmacy educators have studied and reported on EP&R education and initiatives across the time period discussed. For example, PharmD students and pharmacists have been incorporated into emergency preparedness drills 52 , pharmacists' roles in assisting in emergency preparedness in long-term care facilities 53 , table-top exercises 54 , and in interprofessional education CPE/CE programs with public health professionals. 55 Other outcomes that can be assessed include the number of students, residents, fellows, and pharmacy professionals receiving awards/scholarships/grants for public health related projects, the number of public health projects conducted by pharmacy students, residents or fellows, and the number of these individuals who publish report, present posters or talks, or disseminate other forms of scholarship related to these projects.…”
Section: Epandr In Pharmacy Educationmentioning
confidence: 99%
“…DeGuire et al 40 Despite the fluctuations in emphasis on public health and EP&R training in the CAPE Outcomes and ACPE Standards, pharmacy educators have studied and reported on EP&R education and initiatives across the time period discussed. For example, PharmD students and pharmacists have been incorporated into emergency preparedness drills 52 , pharmacists' roles in assisting in emergency preparedness in long-term care facilities 53 , table-top exercises 54 , and in interprofessional education CPE/CE programs with public health professionals. 55 Other outcomes that can be assessed include the number of students, residents, fellows, and pharmacy professionals receiving awards/scholarships/grants for public health related projects, the number of public health projects conducted by pharmacy students, residents or fellows, and the number of these individuals who publish report, present posters or talks, or disseminate other forms of scholarship related to these projects.…”
Section: Epandr In Pharmacy Educationmentioning
confidence: 99%
“…The study found that even though hospitals held disaster courses and trainings every year, nurses had a worryingly low level of disaster competence, which correlated with their low motivation to participate in disaster rescue. Providing realistic disaster training using simulations, tabletop exercises [40,41], and virtual reality/augmented reality/mixed reality exercises may improve individuals' interests and understanding about disaster situations and disaster knowledge and skills. This would further increase nurses' confidence in disaster management.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…- 31 Repeated training may also serve to reinforce and further encourage preparedness, thus enhancing the capacity for an effective response. Although highly structured, simulation-based training that involves many system players may be highly valued, smaller-scale learning activities involving tabletop simulations 32 and exercises targeting low-intensity, high-frequency events 33 are also likely to prove beneficial. Our work could also conceivably be adapted by community pharmacists, who do not operate as part of a broader organizational plan like their counterparts working in hospitals, 7 to initiate a limited form of training at the level of their individual pharmacy (eg, to simulate a power outage affecting their neighborhood for several hours).…”
Section: Discussionmentioning
confidence: 99%